Упростите выражение: (p+6)(6-p)+(p+2) (c-4)^2-(c-10)(c+10) (x+3)(x-3)-(x+5)^2 (1-2y)^2(2y-3)(2y+3)

Упростите выражение: (p+6)(6-p)+(p+2) (c-4)^2-(c-10)(c+10) (x+3)(x-3)-(x+5)^2 (1-2y)^2(2y-3)(2y+3)
Гость
Ответ(ы) на вопрос:
Гость
1. -p(во 2 степени) + 7p + 38 2. = 116 3. = 16 4. -17 x 32y ( во 2 степени ) 
Гость
(p+6)(6-p)+(p+2)=6р-р^2+36-6р+р+2=-p^2+5p+38 (c-4)^2-(c-10)(c+10)=c^2-8c+16-c^2-10c+10c+100=116-8c (x+3)(x-3)-(x+5)^2=x^2-3x+3x-9-x^2-10x-25=-10x-25  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы